The Effect of Cyanide Concentration and Grinding Time in Tailings on %Extraction at PT. Agincourt Resources - Rakatta Banurea, Andromeda Sanjesti; Nahdi, Sabrina Almasari; Wahyuningsih, Tri (Journal of Metallurgical Engineering and Processing Technology, 2025)
This study aims to analyze the effect of cyanide concentration and ore grinding on the extraction of gold and silver. The tests were conducted on three different samples, including samples without grinding and samples with grinding sized untill 75 µm. The results of the Atomic Absorption Spectroscopy (AAS) test showed that gold content decreased in all samples, while silver content tended to increase. For the Grinding Time test used to achieve a P80 particle size (where 80% of particles pass through a sieve at certain size), it was found that the optimal time to reach 75 µm was 18 minutes and 65 seconds. Silver extraction increased with the addition of cyanide concentration up to 1000 ppm and grinding untill 75 µm, while gold extraction remained insignificant (0%). This is likely due to the short duration of the test, which only for 2 hours using the bottle roller test method. For future tests, it is recommended to use a stir leach or magnetic stirrer with longer duration of stirring time and better control of oxygen and pH levels. The test results showed that the percentage of silver extraction was 0,82%, 3,23%, and 3,28%, respectively, while the percentage of gold extraction was 0%. The AAS test revealed that gold content ranged from 0,001 g/t to 0,003 g/t, while silver content ranged from 0,322 g/t to 0,559 g/t. The most influential parameters for increasing silver extraction were ore size reduction and the addition of cyanide concentration.